Business Plan on Establishment of Putche Mix Dessert Delicacy in Fairview, Commonwealth Avenue, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Dessert is a part of Philippine cuisine and even in other countries. It is usually eaten after the meal and mostly it is a sweet kind of food. Putche Mix Dessert Delicacy is a business that offers puto and leche flan in separate and in mix processes and has added offer design to product, put toppings, and combine with fruits. It has customized and personalizes products for customer consumption. The proposed business aims to extend the expectation of everyone with the common food Puto and Leche Flan into an innovation and delicate and to be one destination and distributor of dessert and to bear in mind that Filipino delicacy will never be been missed and will be more interesting as time goes by. The business targeted individuals, groups, and businesses composed of families, employees, couples, canteen in schools, eatery, catering services, buffet, and restaurants. The business utilized a descriptive method of research. The proponents surveyed100 respondents around the location at Commonwealth Avenue, Fairview Quezon City and used a survey questionnaire to analyze and test the market viability of the business in terms of product, price, place, and promotion. The study also utilizes financial statements and financial conditions that test the level of profitability of the business. The respondents were between 13 and 40 years old, with 74% and 26% of 40 years old above. Based on the response of the respondents, the product should be consumable in terms of product, price, place, and promotion. The researchers found out that possible customers will range from 13 to 40 years old, thereby determining that customer interest and capability to avail on these ages. The financial aspect of business determined the annual revenue and the ROI in five years of comparative financial statements. The result was the business gain acceptability and possible growth. To improve the business, researchers recommended to add valuable meal that is to be pair in dessert, provide combos and sizes with new pricing strategy, develop more ideas for innovation of design to more the attraction of customers for its competitive advantage. A plan and strategy of promotion and distribution for the expansion of the business if investment return and entirely to growth. The financial aspect of the business should always monitor its status. This factor is important in running the business to be able to be a profitable company. Good work conduct and quality of product and service should always be before customer satisfaction.
Keywords: dessert, mix, delicacy